Digital Marketing And Branding Analysis : Competitive Advantages Of Small Medium Enterprise Post-Covid-19 - Rizqon Jamil Farhas; Zulfan Ependi (Journal of Engineering Science and Technology Management (JES-TM), 2022)
This study aims to analyze the influence of digital marketing and branding on turnover and competitive advantage of Micro, Small and Medium Enterprises (UMKM) fostered by Universitas Pahlawan Tuanku Tambusai after covid-19. The analytical tool used is WarpPLS with a total sample of 114 SMEs. The results of the study found that Digital Marketing had a positive influence on turnover, and the p value of Digital Marketing had an effect but not significant on turnover with a value of 0.140 (> 0.05). while the influence of Digital Marketing on competitive advantage has a coefficient value of 0.297, meaning that Digital Marketing has a positive effect on competitive advantage. For the influence between Branding and Turnover with a path coefficient value of 0.227, it means that Branding has a positive effect on Turnover but is not significant with a p value of 0.297. While the direct influence of branding on competitive advantage has a negative value of -0.253 meaning that branding does not have a positive influence on competitive advantage with a p value of 0.242. To see the direct effect of Turnover on Competitive Advantage, a positive value of 0.325 was obtained, meaning that Turnover had a positive effect on Competitive Advantage but not significant with a p value of 0.231 (> 0.05).